2019
DOI: 10.12688/f1000research.18493.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Paradoxical acrodermatitis of Hallopeau-like eruption following anti-IL-17 therapy

Abstract: Psoriasis is a chronic immune-mediated inflammatory disease. Up to 40% of patients with psoriasis may develop psoriatic arthritis.  Currently, interleukin (IL)-17/IL-23 pathways are identified as key factors in the immunopathogenesis of both conditions. Here we describe the case of a patient who developed psoriasiform skin lesions 10 months after the initiation of anti-IL17 therapy for psoriatic arthritis. The underlying disease had responded well to the therapy, but the patient developed a striking pustular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…2 Moreover, Cicogna et al reported a case diagnosed as plaque psoriasis, which developed paradoxical ACH-like eruption after accepting anti-IL-17 therapy. 3 IL-17A inhibitors were effective for patients' cutaneous erythema and pustules, but ineffective for dactylitis. 4,5 The immune system of the nail differs strikingly from that of the skin, with decreased MHC II expression on Langerhans cells, reduced number and function of NK cells and enhanced expression of NK regulators.…”
Section: Patientmentioning
confidence: 94%
“…2 Moreover, Cicogna et al reported a case diagnosed as plaque psoriasis, which developed paradoxical ACH-like eruption after accepting anti-IL-17 therapy. 3 IL-17A inhibitors were effective for patients' cutaneous erythema and pustules, but ineffective for dactylitis. 4,5 The immune system of the nail differs strikingly from that of the skin, with decreased MHC II expression on Langerhans cells, reduced number and function of NK cells and enhanced expression of NK regulators.…”
Section: Patientmentioning
confidence: 94%
“…We found another case report of a 52‐year‐old woman with psoriatic arthritis treated with secukinumab for 9 months who developed a painful eruption with pustules, scaling and tender swelling on the fingers of both hands, diagnosed as ACH‐like paradoxical reaction to an anti‐IL‐17 molecule 9 …”
Section: Discussionmentioning
confidence: 97%
“…8 We found another case report of a 52-year-old woman with psoriatic arthritis treated with secukinumab for 9 months who developed a painful eruption with pustules, scaling and tender swelling on the fingers of both hands, diagnosed as ACH-like paradoxical reaction to an anti-IL-17 molecule. 9 Another documented paradoxical reaction was in fact a localized exacerbation of the psoriatic eruption triggered by secukinumab, but the authors were unable to determine whether the paradoxical reaction was caused only by secukinumab or whether other biologics, including infliximab and brodalumab, had also a partial influence, due to the fact that the patient had multiple biologic switches. 10 EL-Komy et al described a case in which secukinumab retreatment was associated with psoriasis flare and pustular eruption in a 46-year-old female.…”
Section: Discussionmentioning
confidence: 99%
“…2 Darüber hinaus berichteten Cicogna et al über einen Fall, bei dem eine Plaque-Psoriasis diagnostiziert wurde und der nach Anti-IL-17-Therapie eine paradoxe ACH-ähnliche Eruption entwickelte. 3 IL-17A-Inhibitoren waren bei Hautrötungen und Pusteln der Patienten wirksam, bei Daktylitis jedoch nicht. 4,5 Das Immunsystem des Nagels unterscheidet sich deutlich von dem der Haut, mit verringerter MHC-II-Expression auf Langerhans-Zellen, verringerter Anzahl und Funktion von NK-Zellen und verstärkter Expression von NK-Regulatoren.…”
Section: Patientinunclassified